Strategies For Delivering Islamic Religious Education Learning Materials in The Post-Truth Era - Nasikhin; Mahfud Junaedi (Research Institute and Community Engagement of IAIN MADURA, 2022)
This study aims to investigate the delivery strategy of Islamic religious education learning materials in the post-truth era in senior high school. This qualitative research with a phenomenological approach relies on in-depth interview data, observation, and documentation. The research participants involved three teachers of Islamic Religious Education and nine students of SMA Islam Al-Azhar 29 Semarang. Data analysis used the Miles and Huberman model through the stages of data reduction, data display and drawing conclusion. The results of the study indicate that the learning organization strategy tends to be against posh-truth. First, resistance to post-truth can be seen from the pattern of scientific learning approaches through problem-based learning models, cooperative learning models, inquiry learning models, quantum teaching learning models, and learning models for improving thinking skills combined with integrated learning methods. The chosen model has been able to instill character education, literacy, HOTS, and 4C as the main components in fighting posh truth. Third, resistance to post-truth is given through a communication model that is polite, courteous, and not easy to spread hoax information. The results of the study recommend that schools need to prepare adequate learning resource facilities and increase teacher professionalism so that the negative impact of post-truth can be minimized in schools. (Penelitian ini bertujuan untuk mengetahui strategi penyampaian materi pembelajaran pendidikan agama Islam era post-truth di SMA. Penelitian kualitatif dengan pendekatan fenomenologi ini mengandalkan data wawancara mendalam, observasi, dan dokumentasi. Partisipan penelitian ini melibatkan tiga orang guru PAI dan sembilan siswa SMA Islam Al-Azhar 29 Semarang. Analisis data menggunakan model Miles dan Huberman melalui tahapan reduksi data, penyajian data dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa strategi organisasi pembelajaran cenderung bertentangan dengan posh-truth. Pertama, resistensi terhadap post-truth dapat dilihat dari pola pendekatan pembelajaran saintifik melalui model pembelajaran berbasis masalah, model pembelajaran kooperatif, model pembelajaran inkuiri, model pembelajaran quantum teaching, dan model pembelajaran peningkatan keterampilan berpikir yang dipadukan dengan metode pembelajaran terpadu. Model yang dipilih telah mampu menanamkan pendidikan karakter, literasi, HOTS, dan 4C sebagai komponen utama dalam memperjuangkan kebenaran. Ketiga, resistensi terhadap post-truth diberikan melalui model komunikasi yang santun, santun, dan tidak mudah menyebarkan informasi hoax. Hasil penelitian merekomendasikan agar sekolah perlu menyiapkan fasilitas sumber belajar yang memadai dan meningkatkan profesionalisme guru sehingga dampak negatif post-truth dapat diminimalisir di sekolah.)